Changes of Morphological, Optical, and Electrical Properties Induced by Hydrogen Plasma on (0001) ZnO Surface. Issue 16 (19th November 2021) - Remes, Zdenek; Artemenko, Anna; Ukraintsev, Egor; Sharma, Dhananjay K.; Buryi, Maksym; Kromka, Alexander; Potocky, Stepan; Szabo, Ondrej; Kulicek, Jaroslav; Rezek, Bohuslav; Poruba, Ales; Micova, Julia; et al.
Abstract : Plasma provides specific adjustment of solid‐state surface properties offering an alternative to high temperature treatment. Herein, hydrogen plasma treatment of monocrystalline (0001) ZnO surface is studied in an inductively coupled plasma reactor with reduced capacitively coupled plasma mode. The crucial role of electrical grounding of the sample holder for plasma etching and related changes in the morphology, optical, and electrical properties of surfaces exposed to electron and ion bombardment are explained. The effects on the chemical composition of the surface are analyzed by X‐ray photoelectron spectroscopy (XPS), optical properties by photoluminescence spectroscopy, topography, roughness, and surface measurements by atomic force microscopy (AFM) and Kelvin probe force microscopy (KPFM). All methods show altered ZnO surface properties before and after plasma treatment strongly depending on the electrical potential of the holder. Abstract : Electrical circuit of ICP reactor with plasma P, quartz chamber wall W, grounded electrostatic shield S, and holder H : a) grounded ( A measures the transient current) or b) separated from ground G by blocking capacitor C and high impedance voltage probe V .